Personagem-rizoma: atualizações do personagem no curta-metragem Kilmayr - Lopes, Tiago Ricciardi Correa (Universidade do Vale do Rio do Sinos, 2008)
This thesis is a research about character in documentary, considering it’s performance in the short-film Kilmayr. This work belongs to Audiovisual research line of Post Graduation in Communication by UNISINOS, this project has as the main objective verifying and comprehending the forms of actualization of the character in the short-film Kilmayr. The methodological processes of this research are taken in contemporary philosophy related to rizoma and cartographic theories operating the concept of multiplicity
Keywords: curta-metragem; personagem; rizoma; cinema documentário; character; rizoma; short-film; cinema-documentary; Ciências Sociais Aplicadas